Handbook of meat, poultry and seafoof quality (Blackwell Pub., 2007)
The Handbook of Meat, Poultry and Seafood Quality commences with a discussion of basic scientific factors responsible for the quality of fresh, frozen and processed muscle foods, especially sensory attributes and flavors. Following sections discuss factors affecting the quality of beef, pork, poultry, and seafood. Under each muscle food, some or all of the following factors affecting the quality are discussed (Publisher description)